Food security, food sovereignty and the special rapporteur: Shaping food policy discourse through realising the right to food. (July 2014) - Sage, Colin
Over the past 6 years, the United Nations special rapporteur on the right to food, Olivier De Schutter, has vigorously defended the case for small-scale and sustainable farming and has helped to establish the political legitimacy of food sovereignty in high-level expert fora. This commentary offers brief reflections on De Schutter's contribution focusing on the welcome shift of emphasis from food to nutritional security as well as his strong support for agroecology. It argues that he has offered a powerful and coherent alternative to the prevailing paradigm of productivism that has helped reshape food policy discourse.